2008
DOI: 10.1007/s00442-008-1190-z
|View full text |Cite
|
Sign up to set email alerts
|

Inventory, differentiation, and proportional diversity: a consistent terminology for quantifying species diversity

Abstract: Almost half a century after Whittaker (Ecol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(205 citation statements)
references
References 108 publications
1
192
0
12
Order By: Relevance
“…To directly compare the α-diversity [within-sample diversity or estimate of species richness (19)] of the samples with differing sequence counts/sampling efforts, we rarefied the data (i.e., randomly picked an equal number of sequence across samples) using QIIME (Quantitative Insights into Microbial Ecology) (20). Rarefaction curves, which show the observed operational taxonomic unit (OTU) richness as a function of pyrosequencing effort, indicated that the sequencing depth was insufficient to wholly capture the diversity present (Fig.…”
Section: S Rrna Gene Sequence Region Impacts Recovered Maize Rhizosmentioning
confidence: 99%
“…To directly compare the α-diversity [within-sample diversity or estimate of species richness (19)] of the samples with differing sequence counts/sampling efforts, we rarefied the data (i.e., randomly picked an equal number of sequence across samples) using QIIME (Quantitative Insights into Microbial Ecology) (20). Rarefaction curves, which show the observed operational taxonomic unit (OTU) richness as a function of pyrosequencing effort, indicated that the sequencing depth was insufficient to wholly capture the diversity present (Fig.…”
Section: S Rrna Gene Sequence Region Impacts Recovered Maize Rhizosmentioning
confidence: 99%
“…b-diversity can be a useful metric when trying to understand patterns of species diversity across spatial scales (e.g., Veech et al 2002, Crist and Veech 2006, Jost 2007, Tuomisto 2010a, b, Anderson et al 2011, and for example, can allow inference about the relative importance of community assembly processes such as those that are more deterministic (niche-related) relative to those that are more stochastic (e.g., Condit et al 2002, Tuomisto et al 2003, Gilbert and Lechowicz 2004, Dornelas et al 2006, Chase 2007. Unfortunately, a large number of the metrics and statistical analyses used to estimate b-diversity are confounded, are not always directly comparable, and may not produce conceptually meaningful values (Jost 2007, Jurasinski et al 2009, Tuomisto 2010a, b, Anderson et al 2011. For example, one of the biggest problems associated with analyses of b-diversity is that using either a multiplicative (c ¼ a 3 b) or additive (c ¼ a þ b) partition, b-diversity is linked to variation in c and a by definition, thus making statistical comparisons of b-diversity among sites or regions confounded by coincident variation in a or c (e.g., Wilson and Shmida 1984, Lande 1996, Koleff et al 2003, Jost 2007, Tuomisto 2010a.…”
Section: Introductionmentioning
confidence: 99%
“…gamma/alpha; Lande, 1996;Veech et al, 2002;Jost, 2007). Recently, Jurasinski et al (2009) have named these measures 'differentiation diversity' and 'proportional diversity', respectively. The overwhelming majority of beta diversity functions from both groups apply to presence-absence data (Vellend, 2001;Koleff et al, 2003;Tuomisto, 2010a, b), including the well-known Jaccard similarity index adapted by Whittaker (1960, p. 320) to this purpose.…”
Section: Introductionmentioning
confidence: 99%